Effects of a Physical Therapy Intervention to Improve the Quality of Life of Visually Impaired People: Development of an Audio–Tactile Exercise Protocol. (July 2021) - Borges Silva, Maristella; Novais Shimano, Suraya Gomes; Lopes de Oliveira, Nuno Miguel
Introduction: The purpose of this study was to develop and implement an audio–tactile protocol for therapeutic intervention in individuals with visual impairments.Methods: The Physiotherapy Protocol for People with Visual Impairment (PP-PVI) was developed following five steps: physiotherapy evaluation, linguistic selection, protocol design, linguistic adequation for visually impaired, and linguistic adequation for English language. Three adolescents and three young adults with visual impairments participated in this longitudinal study and performed the protocol of therapeutic exercises twice a week for 12 months while being evaluated with respect to their quality of life before and after. The quality of life was evaluated using the 36-item Short Form Health Survey (SF-36).Results: The median score for all domains of the quality of life questionnaire improved after PP-PVI, with the exception of the body pain domain, which remained unchanged.Discussion: The PP-PVI was shown to be an important method of therapeutic intervention, and it was easy to understand and apply in persons with visual impairments.Implications for practitioners: The exercises of the PP-PVI facilitate the development of several physical and functional capabilities that are important to the independence of individuals with visual impairments.